Effects of using enhanced biofertilizer containing N-fixer bacteria on patchouli growth - Norhazimah, Abdul Halim (2009)
Producing effective biofertilizer is crucial for environment and future demands while patchouli is important essential oil plants in the world. The objective of this study was to evaluate the effect of enhancing biofertilizer with N-fixer bacteria by applying on patchouli plant. In this study, growth profile of screened N-fixer bacteria is obtained to harvest highest yield of active bacteria. Then, N-fixer strain is added in purchased biofertilizer using peat moss carrier. After 2 weeks, the nitrogen content is determined by Kjeldahl method. The effectiveness of this modified biofertilizer is indicated by average physical changes of plants. From analysis, it was found that nitrogen content of biofertilizer is increased linearly with the increase of N-fixer percentage inoculum. Using biofertilizer can offer yield as good as using chemical fertilizer if complex biofertilizer containing different strain is used. Application of enhanced biofertilizer on patchouli showed improvement of leaves and branch growth up to 8% and 5% respectively compared to original biofertilizer. The suitable range of N-fixer inoculum should be applied to biofertilizer is more than 10%.-Author-